A research model for open innovation: synthesizing opportunities and challenges surrounding SMEs - Rahman, Md. Hakikur (2011)
With the advent of innovative technologies and long the setting of entrepreneurship development philosophy, context and business handling have been transformed from being traditional to innovative. Depending on diversity and nature of the transformation, innovation has been shifted from closed peripheries to open dimension. Looking at the immense benefits, ranging from small entrepreneurs to corporate to multinational, business houses are adopting various innovation techniques. However, the road to innovation, despite being a paradigm shift is not smooth and ready for many, particularly the small and medium enterprises (SMEs) who mainly deal with the clients at the outer peripheries of the social circle. Moreover, there is a research gap within the context of SME development through open innovation strategies. This chapter intends to initiate a research model for carrying out research on the development of SMEs through utilization of open innovation strategies. Along these contexts it has tried to synthesize aspects of opportunities and challenges surrounding SMEs development utilizing open and collaborative approaches. To set the research model, the paper has developed an innovation opportunity framework, both at the policy level and at the entrepreneur level. To validate the research hypothesis, the chapter hints at carrying out a three phase survey comprising selected SMEs.